2013
DOI: 10.1016/j.scriptamat.2012.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic recrystallization mechanisms of an Fe–8% Al low density steel under hot rolling conditions

Abstract: Iron-aluminium alloys display promising physical and mechanical properties. In this study, the effects of strain, strain rate and temperature on an Fe-8% Al were investigated. Hot torsion tests were performed in the temperature range 900-1100 °C and strain rate range 0.1-10 s À1 . In this alloy, two types of dynamic recrystallization may operate during hot deformation: at high temperature and high strain rate, this alloy undergoes discontinuous dynamic recrystallization, whereas at lower temperature and strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(45 citation statements)
references
References 11 publications
5
40
0
Order By: Relevance
“…Previous studies have shown that the recrystallization occur while the alloys are hot-rolled at high temperature, which result in subgrains [23][24][25]. Castan et al also pointed out that the recrystallization readily occurred after the original grain boundaries were elongated and broken up during hot rolling process [10]. The results of the studied alloys were similar to the study by Castan [10].…”
Section: Microstructure Evolutionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies have shown that the recrystallization occur while the alloys are hot-rolled at high temperature, which result in subgrains [23][24][25]. Castan et al also pointed out that the recrystallization readily occurred after the original grain boundaries were elongated and broken up during hot rolling process [10]. The results of the studied alloys were similar to the study by Castan [10].…”
Section: Microstructure Evolutionsupporting
confidence: 82%
“…Moreover, heat processing technology can optimize the microstructure and mechanical properties by controlling the phase composition and precipitation of compounds [9]. Castan [10] studied the microstructure evolution of Fe-8% Al low density steel under hot rolling conditions. The study showed that the recrystallized grain occurred at the suitable hot rolling temperature.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, it is important to investigate the deformation behavior of the steels at elevated temperature since the thermomechanical processing is a devoted part of steel production. In contrast to the amount of researches dedicated to the physical metallurgy of low-density steels, the conducted studies on their hot deformation behavior are quite rare [19,20]. Castan et al [19] have shown that the dynamic recrystallization (DRX) operates as the dominant restoration mechanism during hot deformation of Fe-9%Al alloy.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the amount of researches dedicated to the physical metallurgy of low-density steels, the conducted studies on their hot deformation behavior are quite rare [19,20]. Castan et al [19] have shown that the dynamic recrystallization (DRX) operates as the dominant restoration mechanism during hot deformation of Fe-9%Al alloy. However, According to Hamada et al [20] the addition of Al to conventional high-Mn TWIP steels retards the onset of DRX to the higher imposed strains.…”
Section: Introductionmentioning
confidence: 99%
“…The texture is weak as well. The typical D2 component f 1 1 2gh1 1 1i expected in torsion tests of ferritic steels [18,22,23] is not observed (Fig. 8).…”
mentioning
confidence: 85%